151k views
4 votes
Helppppppppppp pleaseeeeeeeeeeeeeeeeeeeeee

Helppppppppppp pleaseeeeeeeeeeeeeeeeeeeeee-example-1
User TheMar
by
5.7k points

2 Answers

6 votes

Answer:

1/6

Explanation:

When dividing by exponents, you need to subtract the exponent from top to bottom. Ex: 5^3/5^2=5^1 which is just one, because you subtract 3 and two. In this case, 6^-2 / 6^-1 gets us 6^-1 which is the same thing as 1/6^1. Because remember, a^-x = 1/a^x.

Hope this helps!

:)

User C Dot StrifeVII
by
5.3k points
2 votes

Answer:

1/6

Explanation:

6^-2 / 6^-1

We know that a^b / a^c = a^(b-c)

6^(-2 - -1) = 6^(-2+1) = 6^-1

We know that a^-b = 1/a^b

1 /6^1 = 1/6

User Musical Shore
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.